Earthquake Preparedness in The Dental Office - Manuel DH Lugito (TALENTA, 2024)
An earthquake is an unpredictable and potentially devastating natural event typically caused by the movement of tectonic plates along fault lines, volcanic activity, or even human-induced events such as nuclear tests. This devastating event has been observed to possess the capability to trigger various secondary hazards, including ground shaking, soil liquefaction, landslides, fissures, avalanches, fires, floods, and tsunamis. Accordingly, in the context of a dental office, earthquakes pose significant risks to the structure of the building, dental equipment, as well as patient records, and can lead to electric shocks, malfunctioning of X-ray machines, exposure to radiating ionization, and fires, all of which can further result in severe injuries, disability, or death. To mitigate the effects of the outlined threats, earthquake preparedness within dental offices is crucial. This includes not only preparation before an earthquake but also the implementation of effective mitigation and evacuation strategies. Earthquake preparedness among dentists and dental staff is essential for safeguarding individuals present in the office, both patients and workers. Therefore, this form of preparedness should comprise risk reduction, evacuation plans, data restoration protocols, recovery efforts, and reconstruction strategies. It is also important to state that providing dentists and dental staff with targeted disaster response training can further enhance individual ability to respond effectively to natural disasters. Written safety and emergency procedures should be reviewed annually, as well as regular drills and practices are promoted to ensure readiness in the event of an earthquake.